2006
DOI: 10.1002/anie.200503538
|View full text |Cite
|
Sign up to set email alerts
|

Mild Ullmann‐Type Biaryl Ether Formation Reaction by Combination of ortho‐Substituent and Ligand Effects

Abstract: An important position: A strong ortho‐substituent effect caused by NHCOR groups in 2‐haloacetanilides in combination with the ligand effect greatly promotes an Ullmann‐type biaryl formation reaction that takes place at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(66 citation statements)
references
References 56 publications
2
63
0
1
Order By: Relevance
“…However, the relatively low reaction temperature [9f, h] required for the coupling with 2-iodoacetanilide indicates that an ortho-substituent effect from the HNCOCH 3 group remained influential during the course of the reaction. Similar results were obtained when other iodides that contain aliphatic and aromatic amido groups were used (Table 1, entries [11][12][13][14][15][16][17], which indicates that the ortho-substituent effect is not limited to the HNCOCF 3 group and that variation at the 2-position of the benzimidazoles is possible by using this method. For the condensation/cyclization reaction, treatment of the coupling-reaction mixture with HOAc generally gave better results than direct heating (Table 1, entries 9-16).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…However, the relatively low reaction temperature [9f, h] required for the coupling with 2-iodoacetanilide indicates that an ortho-substituent effect from the HNCOCH 3 group remained influential during the course of the reaction. Similar results were obtained when other iodides that contain aliphatic and aromatic amido groups were used (Table 1, entries [11][12][13][14][15][16][17], which indicates that the ortho-substituent effect is not limited to the HNCOCF 3 group and that variation at the 2-position of the benzimidazoles is possible by using this method. For the condensation/cyclization reaction, treatment of the coupling-reaction mixture with HOAc generally gave better results than direct heating (Table 1, entries 9-16).…”
supporting
confidence: 80%
“…[10] During studies on the CuI-catalyzed assembly of diaryl ethers using amino acids as ligands we discovered that there is an ortho-substituent effect directed by NHCOR groups in Ullmann-type C À O bond formations. [11] Further explorations revealed that the same effect exists in the coupling of aryl halides with activated methylene compounds. [12] We were interested in whether this effect could promote aryl amination to afford ortho-aminoanilides at low reaction temperatures, which in turn would provide 1,2-disubstituted benzimidazoles through an intramolecular condensation.…”
mentioning
confidence: 98%
“…[5p] Palladium-or copper-catalyzed intramolecular O-arylations have attracted much attention, and some oxygen heterocycles were constructed with the Ullmann-type O-arylation strategy, [6] for example copper-catalyzed synthesis of substituted 4H-1-benzopyrans (Scheme 1 b),…”
mentioning
confidence: 99%
“…Generally, both electron-rich and electron-deficient phenols were compatible with these reaction conditions, delivering the corresponding diaryl ethers with good to excellent yields (Entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Noteworthy is that some sterically hindered phenols, such as 2-substituted phenols and 2,4,6-trimethylphenol, also worked well to provide 3k-3n in about 70% yield (Entries 10-13).…”
Section: Resultsmentioning
confidence: 99%
“…We have discovered that there is an ortho-substituent effect directed by amido groups in copper-catalyzed diaryl ether formation 8 and other related coupling reactions. 9 In our previous reports, only aryl bromides and iodides were examined.…”
Section: Introductionmentioning
confidence: 99%